Analisis Pemanfaatan Hutan Mangrove dan Kontribusinya Terhadap Pendapatan Rumah Tangga Masyarakat di Pulau Tanakeke Kabupaten Takalar - Saputro, Alief; Nyompa, Sukri; Arfan, Amal (LaGeografia, 2019)
This research is a type of qualitative research with the sampling technique used was purposive sampling with a sample size of 38 respondents. Data collection techniques used are 1) observation techniques, 2) interview techniques, 3) documentation techniques. The results of this study are 1) the people of Tanakeke Island, Takalar Regency use the mangrove forest as a place to meet the needs and improve the family's economy or take fisheries resources to be marketed, some people use the magrove forest to take firewood and some are included in the farmer group, 2) Tanakeke Island community Takalar Regency manages mangrove forests with mangrove nursery activities, participates in mangrove planting on its own / group / agency initiative, cleansing land for mangrove planting activities and the community manages mangrove forests by caring for mangrove ecosystems that have been planted, 3) Contribution of forests mangrove by 66.13% of the household household income on Tanakeke Island, Takalar Regency.